Design and development of a single phase power system simulator - Afshari, Esmail Ghelich (1986)
To expand the range of certain experiments which are quite important in the realization of the behavior of power systems under certain circumstances, a need for a certain simulator that could react similarly to an actual plant becomes very important. The Single Phase Power Simulator (SPPS) makes the realization of certain important experiments possible in the laboratory, which in turn helps in analyzing the behavior of the system as a certain piece of equipment is incorporated into the simulator, or as certain parameters are varied throughout the system. Power and relay simulation, which are readily performed using the Single Phase Power Simulator, are two very important fields in power system studies, where each of the abovementioned fields is divided into several categories which are in themselves quite important in the design and operation of power systems.
Typescript.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Single phase power simulator; Single phase power simulator